Public relations and communication for an environmental crisis: the case of Andalusian universities - Marín Ruiz, Antonio; Durán Mañes, Ángeles; Fernández Beltrán, Francisco (Historia y Comunicación Social, 2014)
The university press offices arose in Spain in the 80s. However, those Spanish offices did not experience the evolution from public relations services into university press offices as in other Western countries. In this article, the growth of functions of existing communication services are discussed, particularly the case of Andalusian universities, as well as the emergence of ICT as elements that suggest the need for the redefinition of the concept of public relations services of institutions in crisis.